The Handling of the Smallpox Outbreak in Cirebon from 1870-1930 - Arkan, Bagas Wahib; Wijayati, Putri Agus (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to produce a narrative about the government's efforts in handling the ongoing smallpox outbreak in Cirebon. Poor living conditions can make it easier for communities to be struck by disease outbreaks. During the Dutch colonial period, infectious diseases caused chaos and concern among the people, one of which was the smallpox epidemic. The spread of smallpox first entered the Java region in the 17th century and reached Cirebon in 1870. The study uses historical methods, namely source collection, critique, interpretation, and historiography. The research focuses on the handling of the smallpox outbreak in Cirebon. This epidemic was triggered by poor sanitation, population density, and regional modernization. The study also highlights the role of vaccination, quarantine, and traditional medicine in efforts to combat the smallpox epidemic, as well as the challenges faced in implementing health policies in the local community. Ultimately, this article shows that efforts to prevent the smallpox outbreak in Cirebon were not entirely effective due to resistance from some parts of the community and poor environmental factors.